The role of information and communications technology (ICT) in supply chain management (SCM) in distributor perspective - a study of distributor company of automotive parts in Klang area - Muhammad Amirul, Zainal Abidin (2013)
An increasing number of researches have been made around Supply Chain Management (SCM) and the types of role Information and Communication Technology (ICT) plays towards SCM. SCM initiatives driven by the role of ICT brings along synchronized workflow of the SCM. However, practical insight to addressing the types of role of ICT play in the SCM in distributor perspective based on real world contemporary studies, are limited. This research aims to investigate the relationship between the role of ICT and SCM in distributor perspective. It aims to examine the types of role play in SCM and to identify the three important basic roles of ICT whether they have significant influence on SCM in distributor perspective. The three roles of ICT which are useful aid, competitive advantage and prerequisite are the independent variables. Each of the independent variables was tested to determine its relationship with SCM in distributor perspective. The questionnaires were sent to 103 respondents to fill it. The participating respondents represented a return rate of 100%. Three (3) hypotheses were developed and tested using Pearson Correlation and Regression Analysis. The findings indicate that each of the respondent in distributor companies of automotive parts in Klang, Selangor find that each role is important towards SCM. There is significant correlation between the three roles of ICT and SCM. They feel that when ICT play as a useful aid, competitive advantage and prerequisite in SCM, their company’s SCM will be significantly influenced by the three roles of ICT. The implications of these findings are discussed and suggestions for future research are also identified and proposed.